The effect of liquidity ratio, activity ratio, and profitability ratio on accounting profit with firm size as a mediation - Nadia Tresna Kurniani (Privietlab, 2021)
One of the important parameters in the financial statements used to measure management performance is profit. Financial ratios as one of the information in the financial statements are used to measure the company's financial performance as proxied by profit. This study aims to analyze the effect of liquidity ratios, activity, and profitability on accounting profit with firm size as a mediating variable on issuers of the consumer goods sector in 2016 - 2020. The research method used is path analysis with the AMOS 23.00 software analysis tool. The results show that the liquidity ratio has no effect on accounting profit, the activity ratio has a significant effect on accounting profit, the profitability ratio has a significant effect on accounting profit, and company size only mediates the liquidity ratio on accounting profit.